Expression of Ki-67 and p63 in Carcinoma of Urinary Bladder - Islam, Mohammad Mazharul; Ali Jinnah, Mohammed Shahed; Karim, Saiyeda Sinthia; Afroze, Farzana; Khatun, Julekha; Islam, Mohammad Ariful (Central Medical College Journal, 2024)
Background: For urinary bladder carcinoma, a specific tumor marker to distinguish the progression of disease is very much needful to ensure early diagnosis and prevent further morbidity. This study was designed to evaluate the expression of Ki-67 and p63 in patients with carcinoma of urinary bladder. Methods: This cross-sectional observational study was conducted at the department of Pathology in Dhaka Medical College Hospital for one year of period following approval of this protocol. A total 36 cases of urinary bladder carcinoma who underwent surgical intervention were enrolled in this study. Written informed consent was ensured from each of the participants. Data collection was done through a structured questionnaire. After collection of all the required data, analysis was done by SPSS 23.0. Results: Mean age of the patients was 56.94±13.46 (SD) years with clear male dominance (88.90% VS 11.10%). High grade tumor was observed in 80.6% of patients and low grade tumor in 19.4% of patients. Higher stage of muscle involvement was observed statistically in high grade tumor. Mean Ki-67 was statistically higher in patients with high grade tumour. But mean p63 was statistically similar in both high and low grade tumors. Conclusion: This study observed significant relation between Ki-67 and tumour grade in patients with urinary bladder carcinoma. Central Medical College Journal Vol 8 No 1 January 2024 Page: 17-22